Investigation on Prosthetic Leg using Design of Experiments (DOE) - SIVAKUMARAN, THANUSKUMARAN; AZLI BIN NAWAWI (Progress in Engineering Application and Technology, 2023)
Wearable technology for prosthetic limbs and replacement organs is a rapidly growing field. A prosthesis is indeed an artificial device intended to replace a missing bodily part caused by trauma, sickness, or a birth defect. Therefore, prostheses are typically intended to replace the missing body organ and restore its functions. The main issues with prosthetic technologies and practices were poor prosthesis comfort and durability. The creation of a prosthetic for people who are missing a lower limb is the aim of this project. This project entails designing and producing a lower limb prosthesis out of local materials to improve the product’s affordability. By developing an inexpensive, cosy, and long-lasting prosthetic, this initiative intends to improve the quality of life for persons who have lost their lower limbs. This study research aims to identify the significant parameters and optimum setting for the spring of the shock absorber. The overall study research methodology consists of a few phases that correspond to the study research objectives, which are constructing a shock absorber pylon model in SOLIDWORKS environment, performing Design of Experiment (DOE) analysis on the spring of the shock absorber pylon and identifying the significant parameters and optimum setting for the spring of the shock absorber pylon.